Plasma Histamine Level as a Distinguishing Factor between Stable Coronary Artery Disease and Acute Coronary Syndrome - I S Prihatiningsih, Prihatiningsih
Abstract Background: Angina can be caused by atherosclerosis in Coronary Artery Disease (CAD) patients either in Stable Coronary Artery Disease (SCAD) or Acute Coronary Syndrome (ACS). Histamine as a mast cell-preformed mediator is suspected to play a role in atherosclerosis. However, its mechanism is yet to be established and there is a lack of these data in the CAD population. To confirm the distinctness of plasma histamine level in patients with Acute Coronary Syndrome and Stable Coronary Artery Disease Patients, this research was an observational analytic study with transversal design in 49 CAD patients by purposive sampling which consists of 25 ACS patients (72% men, mean age 55,6±9,66 years) and 24 SCAD patients (83,3% men, mean age 52,71±8,03 years). The level of plasma histamine was measured using a Histamine ELISA-Kit. Median values of plasma histamine level in ACS group and SCAD group were 30,79 ng/ml (5,85-36,09 ng/ml) and 26,42 ng/ml (0,30-41,39 ng/ml). Comparison analysis on the median value of plasma histamine level between two groups was done with Mann-Whitney U Test and showed a statistical difference between two groups (p=0,011). There are significant differences in plasma histamine level between Acute Coronary Syndrome and Stable Coronary Artery Disease Patients.